Dynamic Ultrasound Assessment of Axial Extensor Mechanism Alignment in Adolescents With and Without Patellofemoral Instability - Elliot M. Greenberg; Bridget DeSandis; Sean Owens; Caroline Kim; Naomi Brown; Brendan Williams; J. Todd R. Lawrence (Orthopaedic Journal of Sports Medicine, 2026)
Background: Patellofemoral instability (PFI) is common among adolescents. Dynamic evaluation of extensor mechanism alignment during early knee flexion may improve the understanding of recurrent instability risk. Purpose: To evaluate the use of point of care ultrasound (POCUS) to dynamically measure axial extensor mechanism alignment in patients with and without PFI. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Patients diagnosed with either patellar subluxation or dislocation and aged between 10 and 18 years were eligible. Control participants included those without any knee pain, nor any history of PFI, fracture, or musculoskeletal developmental disorder. Axial extensor mechanism was visualized with POCUS and the distance between the midpoint of the patellar tendon and lateral trochlear ridge (MPT-LTR) and lateral edge of the patellar tendon and LTR (LPT-LTR) was measured under 4 conditions: (1) active knee hyperextension (ie, quadriceps set), (2) full passive extension, (3) 15° of knee flexion, and (4) 30° of knee flexion. Univariate statistical analyses compared MPT-LTR and LPT-LTR distances across cohorts and knee positions. The area under the curve (AUC) evaluated measurement performance. Results: The cohort (PFI; n = 19) and controls (n = 19) were similar with respect to age, height, and weight ( P > .05). In both groups, the MPT-LTR and LPT-LTR were greatest in active hyperextension and progressively medialized with increasing knee flexion. Patients with PFI demonstrated statistically significantly more lateral MPT-LTR and LPT-LTR distance in all testing conditions ( P ≤ .01) when compared with controls. AUC analysis demonstrated acceptable performance across measures, ranging from 0.712 to 0.837. Conclusion: Patients with PFI consistently exhibited a more laterally oriented patella while performing active knee hyperextension and throughout the first 30° of knee flexion when measured using a novel POCUS evaluation.